Analysis of The Accounting Information System for The Procurement of Food Raw Materials at Nutritional Support Units (SPPG) Under The Free Nutritious Meals Program: A Multi-Site Case Study in West Java - Juwita, Tita; Christina, Veronica (Journal of Economics and Business UBS, 2026)
The Free Nutritious Meals Program (Program Makan Bergizi Gratis/MBG), administered by Indonesia’s National Nutrition Agency (Badan Gizi Nasional/BGN), positions Nutritional Support Units (Satuan Pelayanan Pemenuhan Gizi/SPPG) as technical implementers responsible for large-scale daily procurement of fresh food ingredients. This study aimed to analyze the conditions, constraints, and effectiveness of internal controls within the food ingredient procurement accounting information system (AIS) at five SPPG units in West Java. The study employed a qualitative approach using a multi-site descriptive case study design involving SPPG Cililin, Cileunyi, Cijaura, Padasuka Cimahi, and Sukamenak. Primary data were collected through semi-structured in-depth interviews with 14 informants, complemented by accounting document reviews and field observations, and analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). The findings indicate that four of the five SPPG units had implemented relatively well-organized procurement AIS practices with varying levels of maturity, whereas SPPG Cililin experienced systemic challenges due to limited human resources. The main determinants of AIS quality were compliance with BGN’s official standard operating procedures, disciplined routine reconciliation processes, and the administrative quality of partner cooperatives. The study also found that BGN had established formal standards and reporting systems that encouraged SPPG reporting compliance through a fund-disbursement incentive mechanism. Based on the COSO (2013) framework, internal controls over procurement at four SPPG units were considered relatively adequate due to layered authorization procedures, although a fully independent verification function had not yet been formally implemented. The study recommends strengthening the dissemination of BGN’s existing AIS standards, enforcing segregation of duties at the SPPG level, and standardizing documentation practices among partner cooperatives.